A Cyanine Dye Encapsulated Porous Fibrous Mat for Naked‐Eye Ammonia Sensing. Issue 16 (3rd August 2016) - Ji, Chendong; Ma, Lijing; Yin, Meizhen; Yang, Wantai; Pan, Kai
Abstract: Electrospun ultrathin fiber‐based sensors are desirable because of their practicality and sensitivity. Ammonia‐detection systems are in high demand in different areas, including the industrial and agricultural fields. However, current technologies rely on large and complex instruments that restrict their actual utilization. Herein, we report a flexible naked‐eye ammonia sensor, the polylactic acid–cyanine (PLA‐Cy) fibrous mat, which was fabricated by blending a carboxyl‐functionalized cyanine dye (D1 ) into electospun PLA porous fibers. The sensing mat was shown to undergo a naked‐eye‐detectable color change from white to blue upon exposure to ammonia vapor. The mat showed high selectivity to ammonia gas with a detection limit of 3.3 ppm. AggregatedD1 was first encapsulated by PLA and was then ionized by NH3 . These mechanisms were examined by photophysical studies and scanning electron microscopy. The aggregation–deaggregation process ofD1 in the PLA‐Cy fibrous mat led to the color change. This work provides a facile method for the naked‐eye detection of ammonia and a novel strategy for the use of organic dyes in ammonia sensing. Abstract : Feeling blue : A polylactic acid porous fibrous mat blended with a cyanine dye is used for ammonia sensing. Upon exposure to ammonia vapor, the aggregated dye deaggregates owing to ionization of the four carboxylic acid groups. Correspondingly, the fibrous mat undergoes a color change from white to blue as a naked‐eye ammonia sensor.